Paleohydrological reconstruction of the Siwalik Group along the Tinau Khola section, west-central Nepal Himalaya - Ulak, Prakash Das (Journal of Nepal Geological Society, 2009)
Neogene fluvial sedimentary sequences of the Siwalik Group are extensively accumulated in the southern frontal part of the Himalaya and well exposed in the Tinau Khola section of the west-central Nepal Himalaya. The group reveals a coarsening upwards succession in general but many fining-upwards fluvial successions on a scale from several to tens of metres is established in each lithological unit. The paleohydrological characteristics have been estimated using thickness of fining upwards fluvial successions, their grain diameters, and bedforms. The paleohydrology suggests an increase in flow velocity, channel slope gradient, and discharge of the fluvial system. Paleovelocity varies from 0.17 to 5.31 m/s, paleochannel gradient and paleodischarge change from l.13x10-5 to 7.33x10-4 m/m and 101 to 104 m3/s, respectively towards the stratigraphic top. These progressively changing paleohydrological characteristics reflect the southward propagation of thrusts caused by the upheaval of the Himalaya.